Exoskeletons: AFM Identification of Beetle Exocuticle: Bouligand Structure and Nanofiber Anisotropic Elastic Properties (Adv. Funct. Mater. 6/2017). (February 2017) - Yang, Ruiguo; Zaheri, Alireza; Gao, Wei; Hayashi, Cheryl; Espinosa, Horacio D.
Abstract : Horacio D. Espinosa and co‐workers present a nanoscale experimental – theoretical methodology to reveal the hierarchical structure and properties of the exoskeleton of arthropods in article number 1603993. As a case study, they characterize the helicoidal fiber structure present in the beetle's elytra and identify the fiber anisotropic elastic constants.